PSMA expression and PSMA PET/CT imaging in metastatic soft tissue sarcoma patients, results of a prospective study. - Kleiburg, F.; van der Hulle, T.; Gelderblom, H.; Slingerland, M.; Speetjens, F. M.; Hawinkels, L. J.A.C.; Dibbets-Schneider, P.; van Velden, F. H.P.; Pool, M.; Lam, S. W.; Bovée, J. V.M.G.; Heijmen, L.; et al. (European Journal of Nuclear Medicine & Molecular Imaging, 2025)
Purpose: Prostate-specific membrane antigen (PSMA) expression has been observed in a subset of soft tissue sarcomas, mainly in the neovascular endothelial cells. This feasibility study aimed to evaluate PSMA expression and PSMA PET/CT imaging in metastatic soft tissue sarcoma, providing important insights for potential future exploration of PSMA-targeted radioligand therapy. Methods: This prospective single-center study included adult patients with metastatic soft tissue sarcoma, with measurable disease (lesion diameter > 1 cm), available biopsy/resection material, ECOG/WHO performance status of 0–2 and either no prior systemic treatment, progressive disease during/after treatment, or stable disease/partial response with the last dose > 8 weeks prior. Immunohistochemical PSMA staining was performed on previously obtained biopsy or resection material. In case of high PSMA expression, a [18F]-JK-PSMA-7 PET/CT scan evaluated tracer uptake, with adequate uptake defined as SUVmax > 8. Results: Of 25 included patients, 11 (44%) had high PSMA expression: 4/11 leiomyosarcomas, 3/4 dedifferentiated liposarcomas, 2/5 undifferentiated pleomorphic sarcomas, 1/2 myxofibrosarcomas and 1/1 malignant peripheral nerve sheath tumour. Five of 11 patients agreed to a [18F]-JK-PSMA-7 PET/CT, of which 3 had lesions that showed adequate tracer uptake (SUVmax 10.7–16.7). However, uptake across all metastatic lesions was highly heterogeneous (median SUVmax = 3.8; range 0.5–16.7), indicating that these patients are unlikely to benefit sufficiently from PSMA-targeted therapy. The study was therefore terminated prematurely. Conclusion: PSMA expression and PSMA tracer uptake in metastatic soft tissue sarcoma were highly heterogeneous. A deeper understanding of PSMA biology and improved patient selection criteria are essential for future application of PSMA-targeted radioligand therapy in this disease. Trial registration: : clinicaltrials.gov, NCT05522257. Registered 31-08-2022.